2020
DOI: 10.1108/ijbpa-10-2019-0094
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy-analytic hierarchy process approach for measuring flood resilience at the individual property level

Abstract: PurposeRecent changes in climate, rainfall patterns, snow melt and rising sea levels coupled with an increase in urban development have increased the threat of flooding. To curb these threats and mitigate these damages, property-level approaches to improving resilience are now being encouraged as part of an integrated approach to flood risk management. This raises questions such as, what are the flood resilient attributes within indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This study can help the drug industry by mitigating the obstacles to sustainability and improved quality manufacturing. [ 3 ] uses a fuzzy AHP approach for the measurement of property level flood resilience. In this work, the significant flood resilient attributes and their sub-attributes were identified by reviewing the literature.The authors then use FAHP methodology to develop a new model ‘Composite Flood Resilient Index’ based on the weightage associated with attributes and the sub-attributes.…”
Section: Overview Of Analytical Hierarchy Process and Fuzzy Analyticamentioning
confidence: 99%
“…This study can help the drug industry by mitigating the obstacles to sustainability and improved quality manufacturing. [ 3 ] uses a fuzzy AHP approach for the measurement of property level flood resilience. In this work, the significant flood resilient attributes and their sub-attributes were identified by reviewing the literature.The authors then use FAHP methodology to develop a new model ‘Composite Flood Resilient Index’ based on the weightage associated with attributes and the sub-attributes.…”
Section: Overview Of Analytical Hierarchy Process and Fuzzy Analyticamentioning
confidence: 99%
“…or even to measure resilience to flooding at property scales [63]. Sometimes system breaking points are revealed.…”
Section: People and The Built Environmentmentioning
confidence: 99%
“…The extent to which various options manage "tolerable risk" can be tested using models of water systems exposed to very large ensembles of climate scenarios [61]. Analytical methods also help to evaluate options for managing urban floods [62], or even to measure resilience to flooding at property scales [63]. Sometimes system breaking points are revealed.…”
Section: People and The Built Environmentmentioning
confidence: 99%
“…Although previous research has attempted to work on resilience, such as Adebimpe et al (2018), Oladokun et al (2017) and Adebimpe et al (2020), the works have been directed to flood resilience at the individual property level. For example, Oladokun et al (2017) identified a wide range of inherent resistance, supporting facilities and resident capacity to define a three-variable mapping system that models a household's flood resilience response; factors that concern the flood-prone community where the individual properties are located were omitted.…”
Section: Introductionmentioning
confidence: 99%
“…Expert opinions were used in rating the input dimensions for the selected communities.Findings -In spite of various inputs from experts in the same study area (Apete, Ibadan, Nigeria), the resulting FIS generated consistent resilience indices for various natural, socio-technical and SEF. This approach can strengthen flood resilience measurement at the community level.Originality/value -Although previous attempts have been made to measure flood resilience at the individual property level (Oladokun et al, 2017;Adebimpe et al, 2020), this research focuses on measuring flood resilience at the community level by adapting the fuzzy logic approach. The fuzzy logic-based model can be a tool for flood resilience measurement at the community level.…”
mentioning
confidence: 99%